Genesis of Pedagogical Views of A. Makarenko on the Collective and Personal Dominants in Education - Valentyna Gresʼkova (Pedagogical Discourse, 2013)
The article is based on the analysis of historical and pedagogical sources which traced the evolution of the educational views of A. Makarenko on the collective and personal dominants in education. The established three groups of values ​​on which his pedagogical system is based are following: the values of personality socialization; the values ​​of personal development, ​​condition values that affect the formation of values ​​of the first and second groups; the peculiarities of teacher positions as for the personal and oriented approach to education, revealed the possibility of using the ideas of A. Makarenko in the realization of personal and oriented approach to education in the modern school.